Fertilization and regrowth age on yield and bromatological composition of Tithonia diversifolia - Arias-Gamboa, Luis Mauricio (2023)
Introduction. Tithonia diversifolia (Hemsl.) A. Gray is a plant with high potential for ruminant feeding, but there is limited research comparing the effects of chemical or organic fertilization at different regrowth ages on its yield and nutritional composition. Objective. To evaluate the effect of the type of fertilizer and the age of regrowth on the yield and nutritional composition of Tithonia diversifolia forage. Materials and methods. The work was conducted in 2020 at the Finca Experimental Santa Lucía of the Universidad Nacional de Costa Rica. A completely randomized divided plot design was employed, with fertilizer type as the main plot and regrowth age as the subplot, with three replicates per treatment. The fertilizer types tested were vermicompost, urea, and a control without fertilizer, with a nitrogen application rate of 150 kg/ha/year. The regrowth ages evaluated were 30, 50, and 70 days for a total of nine treatments. The variables evaluated were biomass production, leaf/stem relation, and nutritional composition. A split plot ANOVA was performed to analyze the data. Results. Among the treatments, the urea treatment with 70 days of regrowth exhibited the highest biomass production (77.18 t/ha of green matter and 7.10 t/ha of dry matter [MS]), while the control treatment with 30 days of regrowth yielded the highest leaf/stem relation (1.77). The type of fertilizer had a significant effect on the variables of MS, crude protein (PC), neutral detergent fiber, and non-fibrous carbohydrates (CNF), whereas regrowth age alone did not significantly affect digestible neutral detergent fiber and CNF. The highest PC content was observed in the urea treatment with 30 days of regrowth (27.61 % PC). Conclusion. Fertilization and regrowth age influenced the yield and bromatological composition of T. diversifolia. These findings contribute to our understanding of optimizing T. diversifolia production for ruminant feeding.